Exploring the human-nature connection and the perceived risk of nature in children. Issue 1 (2nd February 2022) - Prasad, Archana; Lal, Pankaj; Wolde, Bernabas; Smith, Meghann; Zhu, Michelle; Samanthula, Bharath Kumar; Panorkou, Nicole
Abstract: We explored the impact of a daytrip for children aged 10-13 (n = 40) to assess perception of nature. Those who perceived risk in nature were 11.25 times more likely to indicate disinterest in spending time outdoors. Those interested in spending time outdoors were 6.9 times more likely to think people should care more about the environment. Experiences before the daytrip and demographics were explored further; composters were less fearful than their counterparts (p = 0.009), as were older children (p = 0.049). These findings suggest introducing tactile experiences and earlier interventions may support children's comfort in nature and environmental stewardship.